Carbamazepine Degradation Mediated by Light in the Presence of Humic Substances-Coated Magnetite Nanoparticles - Aparicio, Francisca (2019)
The use of iron-based nanomaterials for environmental remediation processes has recently received considerable attention. Here, we employed core-shell magnetite-humic acids nanoparticles as a heterogeneous photosensitizer and iron source in photo-Fenton reaction for the degradation of the psychiatric drug carbamazepine (CBZ). CBZ showed low photodegradation rates in the presence of the magnetic nanoparticles, whereas the addition of hydrogen peroxide at pH = 3 to the system drastically increased the abatement of the contaminant. The measured Fe2+ and Fe3+ profiles point to the generation of Fe3+ at the surface of the nanoparticles, indicating a heterogeneous oxidation of the contaminant mediated by hydroxyl radicals. Products with a higher transformation degree were observed in the photo-Fenton procedure and support the attack of the HO• radical on the CBZ molecule. Promising results encourage the use of the nanoparticles as efficient iron sources with enhanced magnet-sensitive properties, suitable for applications in photo-Fenton treatments for the purification of wastewater.